ANALISIS SISTEM PENGEMBALIAN ATAU PENUKARAN PRODUK KADALUWARSA DALAM PRESPEKTIF ETIKA BISNIS ISLAM PADA PT ESSEI PERBAMA DI VILLA MUTIARA CIKARANG SELATAN - Rositadani, Yuni Tampi; Astuti, Fitri (Jurnal Al-fatih Global Mulia, 2022)
In buying and selling distributors, there is a possibility that the product will expire or be damaged. Distributor attempts to accept Returns due to expiration or damage by the buyer. In this case the replacement and exchange can be interpreted as khiyar in replacing the goods in the sale and purchase. Where goods that have been purchased can be returned if the item is defective and expired in accordance with the written agreement. This system is intended so that traders do not bear much loss and still trust the goods. The application of this return system has been widely implemented in stores because most traders are currently only focusing on sales without caring about the return system, so distributors and traders will feel safe with their merchandise. So the purpose of this writer is to find out about the return or exchange of expired products according to the perspective of Islamic Business Ethics at PT Essei Perbama. Buying and selling is an act or transaction that has been prescribed in the sense that there is already a law in Islam. The legal basis for buying and selling comes from the Qur'an, hadith and ijma. Therefore all buying and selling transactions must be in accordance with Islamic rules. This research method is collected by interviews, observation, documentation. The data sources used are primary and secondary. Data collection techniques were carried out by means of triangulation (combined), data analysis was inductive/qualitative in nature, data analysis used a descriptive qualitative approach by examining the practice of buying and selling bakery products at PT Essei Perbama. The results of this study conclude: First, the reality of replacing goods in buying and selling at PT Essei Perbama is due to expired and damaged goods encountered by shop buyers (khiyar disgrace and khiyar ru'yah) or because the product is not selling well (khiyar conditions). When viewed from Islamic business ethics, in buying and selling distributors at PT Essei Perbama there is the principle of monotheism where everything is done solely for the sake of Allah, the principle of justice where the seller is, the principle of freedom where the buyer can exchange goods that have defects or even do not sell, the principle responsibility in which the seller is responsible for goods that are not suitable or defective and the principle of good faith which is realized by carrying out transactions based on good faith, transparent and not harming / tyrannizing other parties. Even so, buyers who deliberately make damaged products that don't sell well are practices of taking other people's rights, tyrannizing one of the parties and including consuming property in a vanity.